Security of decision support systems based on decentralized data platforms - Савченко, М. М. (Інститут проблем реєстрації інформації НАН України, 2023)
In the realm of modern information systems, the security of high-risk decision support systems (DSS) handling critical data remains a pressing concern. The accuracy and reliability of DSS outcomes are heavily reliant on the integrity of the data they process, necessitating a highly secure and transparent data platform. Traditionally, many such systems have been centralized, stored in a single location, making them susceptible to data loss and tampering by potential bad actors possessed insider knowledge. This research delves into approaches to address these security challenges by harnessing the potential of decentralized data platforms, with a particular focus on blockchain technology. By embracing blockchain and decentralized data frameworks, DSS can significantly enhance their security model and overall efficiency. The investigation provides a comprehensive overview of blockchain technology, its various types, and the consensus algorithms that underpin its operation. Specifically, the research explores how blockchain can revolutionize the process of data entry by experts who interact with the DSS. By leveraging the inherent immutability and transparency of blockchain, data input becomes more reliable, reducing the risk of fraudulent alterations and ensuring a trustworthy decision-making process. To tackle the issue of scalability, the research proposes a solution of storing only a fraction of the information on the decentralized ledger. This approach guarantees data verification without burdening the system with excessive storage requirements. In summary, this research demonstrates how decentralized data platforms, particularly blockchain, hold the key to fortifying the security and reliability of decision support systems. By embracing these innovative technologies and methods, decision support systems can empower organizations to make well-informed, secure, and tamper-resistant decisions while ensuring data integrity, immutability, and fault tolerance at the platform level.